COSMETIC OR DERMATOLOGICAL EMULSION COMPRISING A MEROCYANINE AND AN EMULSIFYING SYSTEM CONTAINING AN AMPHIPHILIC POLYMER COMPRISING AT LEAST ONE 2-ACRYLAMIDOMETHYLPROPANESULFONIC ACID UNIT - ROUDOT, ANGELINA; SUIDA-BATISTA, ALEXANDRA; CANDAU, DIDIER; LALLORET, FLORENCE (2014)
The present invention relates to a cosmetic or dermatological composition in emulsion form, comprising, in a physiologically acceptable support: a) at least one aqueous phase, and b) at least one oily phase, and c) at least one merocyanine compound of formula (1) or one of the E/E- or E/Z-geometrical isomer forms thereof, in which: R is a C1-C22 alkyl group, a C2-C22 alkenyl group, a C2-C22 alkynyl group, a C3-C22 cycloalkyl group or a C3-C22 cycloalkenyl group, the said groups possibly being interrupted by one or more O, and d) at least one emulsifying system containing at least one amphiphilic polymer comprising at least one 2-acrylamidomethylpropanesulfonic acid unit. Another subject of the present invention consists of a non-therapeutic cosmetic process for caring for and/or making up a keratin material, comprising the application, to the surface of the said keratin material, of at least one composition according to the invention as defined above. The invention also relates to a non-therapeutic cosmetic process for limiting the darkening of the skin and/or improving the colour and/or uniformity of the complexion, comprising the application, to the surface of the keratin material, of at least one composition as defined previously. The invention also relates to a non-therapeutic cosmetic process for preventing and/or treating the signs of ageing of a keratin material, comprising the application, to the surface of the keratin material, of at least one composition as defined previously. La présente invention concerne une composition cosmétique ou dermatologique sous forme d'émulsion, comprenant, dans un support physiologiquement acceptable: a) au moins une phase aqueuse, et b) au moins une phase huileuse, et c) au moins un composé mérocyanine de formule (1) ou l'une des formes isomères à géométrie E/E ou E/Z de celui-ci; dans cette formule, R représente un grouipe alkyle C1-C22, un groupe alcényle C2-C22, un groupe alcynyle C2-C22, un groupe cycloalkyle C3-C22 ou un grouipe cycloalcényle C3-C22, ces groupes pouvant être éventuellement interrompus par ou ou plusieurs O, et d) au moin un système émulsifiant contenant au moins un polymère amphiphile comprenant au moins une unité d'acide 2-acrylamidométhylpropanesulfonique. La présente invention concerne également un procédé cosmétique non thérapeutique pour entretenir et/ou maquiller une matière kératinique, comprenant l'application sur la surface de ladite matière kératinique, d'une composition telle que définie plus haut. L'invention concerne également un procédé cosmétique non thérapeutique pour limiter le noircissement de la peau et/ou pour améliorer la couleur et/ou l'uniformité du teint, comprenant l'application sur la surface de la matière kératinique, d'au moins une composition telle que définie plus haut. L'invention concerne également un procédé cosmétique non thérapeutique pour prévenir et/ou traiter les signes de vieillissement d'une matière kératinique, lequel procédé consiste à appliquer sur la surface de la matière kératinique au moins une composition telle que définie plus haut.